Delineating the Association between Heavy Postpartum Haemorrhage and Postpartum Depression - Eckerdal, Patricia; Kollia, Natasa; Löfblad, Johanna; Hellgren, Charlotte; Karlsson, Linnea; Högberg, Ulf; Wikström, Anna-Karin; Skalkidou, Alkistis (PLOS ONE, 2016)
Objectives To explore the association between postpartum haemorrhage (PPH) and postpartum depression (PPD), taking into account the role of postpartum anaemia, delivery experience and psychiatric history. Methods A nested cohort study (n = 446), based on two population-based cohorts in Uppsala, Sweden. Exposed individuals were defined as having a bleeding of ≥1000ml (n = 196) at delivery, and non-exposed individuals as having bleeding of <650ml (n = 250). Logistic regression models with PPD symptoms (Edinburgh Postnatal Depression scale (EPDS) score ≥ 12) as the outcome variable and PPH, anaemia, experience of delivery, mood during pregnancy and other confounders as exposure variables were undertaken. Path analysis using Structural Equation Modeling was also conducted. Results There was no association between PPH and PPD symptoms. A positive association was shown between anaemia at discharge from the maternity ward and the development of PPD symptoms, even after controlling for plausible confounders (OR = 2.29, 95%CI = 1.15–4.58). Path analysis revealed significant roles for anaemia at discharge, negative self-reported delivery experience, depressed mood during pregnancy and postpartum stressors in increasing the risk for PPD. Conclusion This study proposes important roles for postpartum anaemia, negative experience of delivery and mood during pregnancy in explaining the development of depressive symptoms after PPH.